University of Florida Potato Variety Trial Spotlight: Goldrush - Mario H. M. L. Andrade; Rodrick Z. Mwatuwa; Christian T. Christensen; Pam Solano; Lincoln Zotarelli (EDIS, 2021)
‘Goldrush’ is a russet potato variety commonly grown for the fresh potato market particularly for baking and boiling. It was selected from the progeny of a cross between ND450-3Russ and Lemhi Russet at North Dakota State University (Johansen et al. 1993). It was released in 1992 from the North Dakota Agricultural Experiment Station. ‘Goldrush’ demonstrates high yield and good tuber characteristics compared to its commercial standard ‘Atlantic’. Tuber production and quality results provided in this spotlight are summarized from various trials conducted by the UF/IFAS Hastings Agricultural and Extension Center from 2005 to 2019, except 2012.